Search for third generation scalar leptoquarks decaying into τb - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; et al. (American Physical Society (APS), 2008)
We have searched for third generation leptoquarks (LQ3) using 1.05fb-1 of data collected with the D0 detector at the Fermilab Tevatron Collider operating at s=1.96TeV. We set a 95% C.L. lower limit of 210 GeV on the mass of a scalar LQ3 state decaying solely to a b quark and a τ lepton. © 2008 The American Physical Society.
Keywords: Fermilab Tevatron Collider; Leptoquarks; Lower limits; Third generations; Tellurium compounds